2016
DOI: 10.1016/j.micres.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community analysis of an industrial wastewater treatment plant in Colombia with screening for lipid-degrading microorganisms

Abstract: The operation of wastewater treatment technologies depends on a combination of physical, chemical and biological factors. Microorganisms present in wastewater treatment plants play essential roles in the degradation and removal of organic waste and xenobiotic pollutants. Several microorganisms have been used in complementary treatments to process effluents rich in fats and oils. Microbial lipases have received significant industrial attention because of their stability, broad substrate specificity, high yields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 65 publications
3
20
0
1
Order By: Relevance
“…Proteobacteria and Bacteroidetes were proved to be the dominant components in this study. Similar results in sediment samples were also found in WWTPs in Colombia and China (Silva-Bedoya et al, 2016; Guo et al, 2017). Within the Proteobacteria phylum, Alphaproteobacteria and Betaproteobacteria class were significantly enriched in W4, whose sampling site is close to the confluence of Ba River and Chan River which is also received wastewater from WWTPs (Zhang et al, 2015).…”
Section: Discussionsupporting
confidence: 84%
“…Proteobacteria and Bacteroidetes were proved to be the dominant components in this study. Similar results in sediment samples were also found in WWTPs in Colombia and China (Silva-Bedoya et al, 2016; Guo et al, 2017). Within the Proteobacteria phylum, Alphaproteobacteria and Betaproteobacteria class were significantly enriched in W4, whose sampling site is close to the confluence of Ba River and Chan River which is also received wastewater from WWTPs (Zhang et al, 2015).…”
Section: Discussionsupporting
confidence: 84%
“…Many researchers concluded that Eurotiomycetes is capable of surviving in extreme conditions and produce extracellular and hydrolytic enzymes [30]. [31]. Dothideomycetes is capable of digesting plant litter.…”
Section: Ilns Volume 74mentioning
confidence: 99%
“…Lipases and microbial strains represent green alternatives for wastewater treatment and can have an effect on reducing the oil and fat content in the wastewater; they may assist in controlling severe pollution problems caused by wastewater. Many previous studies have reported the use of lipolytic enzymes for wastewater treatment (Sarac and Ugur, 2015; Silva-Bedoya et al, 2016; Hu et al, 2018). …”
Section: Introductionmentioning
confidence: 99%